2016
DOI: 10.3233/blc-160057
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Symptom Burden in Bladder Cancer: An Overview of Bladder Cancer Specific Health-Related Quality of Life Instruments

Abstract: Background: A key component to monitoring and investigating patient QOL is through patient reported health related quality of life (HRQOL) outcome measures. Many instruments have been used to assess HRQOL in bladder cancer and each instrument varies in its development, validation, the context of its usage in the literature and its applicability to certain disease states.Objective: In this review, we sought to summarize how clinicians and researchers should most appropriately utilize the available HRQOL instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
0
31
0
3
Order By: Relevance
“…Our present review found more support for the BCI, as it was more frequently evaluated in research and scored more favourably using COSMIN. However, the BCI is not without flaw, as evidence has suggested it may be difficult to interpret in circumstances where function and bother scores are different for a domain, under which circumstances researchers must choose whether HRQL should be determined by symptoms (function) or importance of symptoms to the patient (bother) . Consequently, it was recommended that a generic or cancer‐generic PROM be administered alongside the BCI .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present review found more support for the BCI, as it was more frequently evaluated in research and scored more favourably using COSMIN. However, the BCI is not without flaw, as evidence has suggested it may be difficult to interpret in circumstances where function and bother scores are different for a domain, under which circumstances researchers must choose whether HRQL should be determined by symptoms (function) or importance of symptoms to the patient (bother) . Consequently, it was recommended that a generic or cancer‐generic PROM be administered alongside the BCI .…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent overview paper of BC PROMs suggests that the FACT‐Bl performs better than indicated in the present review. The authors state each new Functional Assessment of Chronic Illness Therapy (FACIT) scale undergoes an assessment of test–retest reliability, responsiveness, and convergent and divergent validity with 50 patients (confirmed by personal correspondence with FACIT, by S.J.M. on 14/09/2017).…”
Section: Discussionmentioning
confidence: 99%
“…Der EORTC-QLQ-BLM30 und der FACT-Bl-Cys sind für den Einsatz nach radikaler Zystektomie konzipiert [10].…”
Section: Erfassung Der Lebensqualität Mittels ‚Patient Reported Outcounclassified
“…In der uro-onkologischen Literatur wird am häufigsten der FACT-Bl für die therapieunabhängige Erfassung der HRQOL bei Patienten mit muskel-und nicht muskelinvasivem UCB verwendet [10].…”
Section: Erfassung Der Lebensqualität Mittels ‚Patient Reported Outcounclassified
“…The higher the score, the higher the QoL. The questions BL4 (I am interested in sex) and BL5 (I am able to have and maintain an erection) are not currently scored (3,4).…”
Section: Fact-vci and Fact-bl-cysmentioning
confidence: 99%